Desenvolvimento de sistemas computacionais móveis integrados a receptores GPS Bluetooth aplicáveis a gestão rural e urbana - Boemo, Daniel (2007)
The advance on areas to the technology has proportionate new forms to create and to store given. Daily, the organizations accumulate given on diverse processes, e many of these, they are worked the field in the format of spread sheets, questionnaires and other ways of survey, restricted the simple notes. With the sprouting of computational devices with reduced dimensions, known as PDA (Personal digital assistants) or Pocket PC, associates to a new paradigm, mobility. The work to follow, it will go to show to the possibility of use of mobile computational systems in the simplification of collection processes and data processing the field, detailing three systems in distinct areas, that they use technology GPS (Global Position System) with connection without wire Bluetooth making possible the geoprocessing of the databases. The areas chosen in question and its respective systems had been the precision farming, Urban Registry and the farm management.